Diagnosis of Tropical Cyclone Structure and Intensity Change - Keyser, Daniel (1999)
The long term goals of this project are to improve and refine understanding of the dynamics of tropical cyclone structure and intensity change, with emphasis on the role of environmental dynamical effects on the intensity change process. This project builds upon the experience of the principal investigator in the study of extratropical cyclone dynamics in maritime regions during the past decade, and the recognition that extratropical maritime cyclones bear similarities to their tropical counterparts. Accordingly, a guiding theme of this research effort is to apply and extend well established dynamical perspectives on extratropical maritime cyclogenesis and cyclone life cycles to the tropics. The long term goals of this project have been addressed through diagnostic and modeling investigations of: (1) the origin and evolution of tropopause based precursor disturbances that culminate in rapid maritime cyclogenesis over the western North Atlantic Ocean; (2) the roles of trough interactions in tropical cyclone intensity change with a view toward determining the factors that distinguish between cyclogenetic and cyclolytic trough interactions; (3) the roles of environmental dynamical effects in tropical cyclone structure and intensity change; and (4) the kinematics of vorticity asymmetries associated with nondivergent barotropic vortices on a beta plane.